Metallothionein family genes in kiwifruit: characterization and determining their roles in plant’s response to different stresses - Liu, Linya; Song, Shuyi; Yang, Na; He, Bin; Xin, Lusheng; Huang, Yacheng (Frontiers in Plant Science, 2024)
Kiwifruit growth and development are affected severely by various biotic and abiotic stresses, especially cold stress and the bacterial disease caused by Pseudomonas syringae pv. actinidiae (Psa).Metallothioneins (MTs) are a group of cysteine-rich proteins that play crucial roles in stress response, metal detoxification, and homeostasis in plants. However, the protective role of these MTs in kiwifruit remains to be elucidated. In the present study, four AcMT genes were identified in the Hongyang kiwifruit genome, including two Type 2 isoforms (AcMT2 and AcMT2a) and two Type 3 isoforms (AcMT3a and AcMT3b) located separately on four different chromosomes. The hormones and stress response cis-elements within the promoter regions of these AcMTs were characterized. It was revealed that the four AcMT genes exhibited different expression patterns in different tissues: AcMT2 and AcMT2a were expressed at much higher levels in the fruit, male flower, female flower, root, and bark, while AcMT3a was expressed mainly in the fruit and AcMT3b was expressed highly in the bark. The expression patterns of these AcMT genes after exposure to Psa infection and different phytohormones, including gibberellic acid A3(GA3), ethylene (ET), and abscisic acid (ABA) were evaluated. It was revealed that in response to Psa infection, the main AcMTs in each tissue (those with expression levels higher compared to the other MTs in that tissue) were downregulated during the early stage in kiwifruits, followed by a recovery phase. In addition, most AcMTs were downregulated after exposure to ET and GA3, while type 2 AcMTs (AcMT2 and AcMT2a) were upregulated after treatment with ABA. The overexpression of AcMTs in Escherichia coli presented a higher tolerance to H2O2, heavy metals, low temperature, and high temperature. Collectively, these findings demonstrated the protecting roles of AcMTs in terms of stress resistance conferred through plant hormone-related signal pathways.